Ubiquitylation functions in the calcium carbonate biomineralization in the extracellular matrix. - Dong Fang (Public Library of Science (PLoS), 2012)
Mollusks shell formation is mediated by matrix proteins and many of these proteins have been identified and characterized. However, the mechanisms of protein control remain unknown. Here, we report the ubiquitylation of matrix proteins in the prismatic layer of the pearl oyster, Pinctada fucata. The presence of ubiquitylated proteins in the prismatic layer of the shell was detected with a combination of western blot and immunogold assays. The coupled ubiquitins were separated and identified by Edman degradation and liquid chromatography/mass spectrometry (LC/MS). Antibody injection in vivo resulted in large amounts of calcium carbonate randomly accumulating on the surface of the nacreous layer. These ubiquitylated proteins could bind to specific faces of calcite and aragonite, which are the two main mineral components of the shell. In the in vitro calcium carbonate crystallization assay, they could reduce the rate of calcium carbonate precipitation and induce the calcite formation. Furthermore, when the attached ubiquitins were removed, the functions of the EDTA-soluble matrix of the prismatic layer were changed. Their potency to inhibit precipitation of calcium carbonate was decreased and their influence on the morphology of calcium carbonate crystals was changed. Taken together, ubiquitylation is involved in shell formation. Although the ubiquitylation is supposed to be involved in every aspect of biophysical processes, our work connected the biomineralization-related proteins and the ubiquitylation mechanism in the extracellular matrix for the first time. This would promote our understanding of the shell biomineralization and the ubiquitylation processes.